Key indicators and determinants in the context of the financial aspects of health systems in selected countries - Sopko, Jakub; Kočišová, Kristína (Adiktologie, 2019)
BACKGROUND: An important part of the monitoring of health is the assessment of the financial aspects of the health system. The assessment of health status and quality of life is important both within an individual country and also in international comparison. The level of education and the health status of the population affect a country's development. The development of a country can also be affected by tobacco and alcohol consumption, which, in addition to its harmful health impact in the form of increased mortality, also has economic consequences for the financial level of households. AIM: We aim to compare the primary indicators used at the OECD level in the case of health assessment. In our work, we focus on demographic, socio-economic, and financial indicators in the health sector, which we then comment on and evaluate from several points of view. METHODS: In our comparative analysis, we focus on the monitoring of health in OECD countries by comparing health spending between 2000 and 2017 and critical health determinants: life expectancy at birth (LE), health-adjusted life expectancy at birth (HALE), the avoidable mortality rate, alcohol and tobacco consumption, etc. We use a two-step cluster analysis for the identification of clusters based on selected indicators. RESULTS: In most countries, we can see a decrease in alcohol and tobacco consumption, which is associated with a decrease in preventable and treatable mortality and infant mortality. The average level of health-adjusted life expectancy for OECD countries in 2016 was 71.1 years. The average level of health expenditure per capita for 2017 was 3856.5 US$. We emphasize the fact that the ageing of the population in many OECD countries will be a challenge not only for the countries' health systems but also for their economies as a whole. CONCLUSIONS: Healthcare expenditure represents a significant part of the use of national resources. Factors such as ageing populations, obesity, harmful alcohol consumption, and tobacco consumption contribute to an increase in the demand for healthcare services. Increased pressure on the use of resources in the health sector is led by key actors and policymakers to look for efficient pathways for the provision of health services.